Government at a Glance 2011. - (:unkn) unknown (Selbstverl., 2011)
This second edition of Government at a Glance almost doubles the number of available indicators of OECD governments performance, to nearly 60. The indicators compare the political and institutional frameworks of government across OECD countries as well as government revenues and expenditures, employment, and compensation. This publication provides evidence for policy makers by measuring the performance of governments in a comparative perspective. This also allows countries to benchmark their performance against other countries. There are also indicators describing government policies and practices on integrity, e-government and open government, and introduce several composite indexes summarising key aspects of public management practices in human resources management, budgeting, procurement, and regulatory management.
Government at a Glance 2011.
Keywords: Partizipation; Regierung; Verwaltung; Ländervergleich; Öffentlicher Sektor; Reformfähigkeit; Indikator; Leistungsfähigkeit; Benchmark